Benefits of Thalassotherapy in the Portuguese Coast: a study in Drosophila melanogaster - Valente, Nuno (2015)
Health tourism is a therapeutic physical and mental well-being, which contemplates the rest and recreation with appropriate therapies such as thalassotherapy, that increase the effects of welfare-induced tourism. The thalassotherapy and balneotherapy constitute a therapeutic strategy that combines the use of baths with sea water, a marine climate, moderate exposure to solar radiation, treatments with sludge and algae-based solutions. In fact, it is a therapeutic strategy commonly used in many countries, including Portugal, not only for the prevention and also for the treatment of various diseases. The biophysical properties of sea water and microbial factors that are contributing to the improvement and treatment of various diseases. Such therapies may therefore have an aging function and a role in cell longevity. Genotoxic/antigenotoxic effects were tested using the Drosophila melanogaster with the Somatic Mutation and Recombination Test (SMART) and comet assay. Results show absence of genotoxic effects of sea water and supplements. The results also demonstrated the ability to reparation of DNA damage in some of the supplements. Indeed, these studies open new doors for the creation of new products with a scientific experimental support and greater efficiency in aging and DNA repair, ensuring preventive potential in skin diseases such as cancer.